2004
DOI: 10.1002/cncr.20005
|View full text |Cite
|
Sign up to set email alerts
|

Large cell neuroblastoma

Abstract: BACKGROUND Among cases of undifferentiated and poorly differentiated tumors in the neuroblastoma (Schwannian stroma–poor) category, the authors histologically identified a group of rare tumors, known as large cell neuroblastomas (LCNs), that are composed of large cells with sharply outlined nuclear membranes and 1–4 prominent nucleoli. METHODS Histologic and immunohistochemical features of LCN were characterized. Morphologic characteristics, clinical features, and MYCN status were compared between LCNs and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 11 publications
1
10
0
4
Order By: Relevance
“…Overall, these data are consistent with previous characterization of the TH-MYCN neuroblastomas and they suggest that the mouse neuroblastomas most closely resembled a class of aggressive human neuroblastoma tumors classified as large cell neuroblastoma [27][29]. This subgroup of tumors is composed of cells that are markedly larger than other NB subgroups and have unique, sharply outlined nuclear membranes and 1–4 prominent nucleoli.…”
Section: Resultssupporting
confidence: 89%
“…Overall, these data are consistent with previous characterization of the TH-MYCN neuroblastomas and they suggest that the mouse neuroblastomas most closely resembled a class of aggressive human neuroblastoma tumors classified as large cell neuroblastoma [27][29]. This subgroup of tumors is composed of cells that are markedly larger than other NB subgroups and have unique, sharply outlined nuclear membranes and 1–4 prominent nucleoli.…”
Section: Resultssupporting
confidence: 89%
“…MYCN amplified pNTs, typically having UH and associated with a poor clinical prognosis, are often characterized as NB-UD/PD having prominent nucleoli [13,14,21]. In the MYCN amplified pNTs, an excess amount of N-myc protein expression and subsequent MYC-MAX heterodimer formation is critical for initiating the molecular mechanism of aggressive behavior by changing the expression of multiple target genes [3033].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, MYCN -amplified tumors typically demonstrate the characteristic histology of neuroblastoma, undifferentiated/poorly differentiated subtype (NB-UD/PD) with a high mitosis-karyorrhexis index (MKI), and are classified into the Unfavorable Histology (UH) group. It is also reported that the presence of prominent nucleoli in neuroblastoma cells is a sign of MYCN amplification [13,14], with a high specificity and a low sensitivity, in pNTs [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Hastalığın ender bir klinik durumu da opsomyoklonus ataksi sendromudur. Başlıca metastaz bölgeleri kemik, lenf düğümü, deri ve karaciğerdir (55)(56)(57) .…”
Section: Peri̇feral Nöroblasti̇k Tümörlerunclassified
“…Ayrıca görüntüleme yöntemleri olarak ultrasonografi, manyetik rezonans görüntüleme ve bazı seçilmiş hastalarda bilgisayarlı tomografiden hasta yönetiminde yararlanılır. Görüntüleme teknikleri ile kitlenin lokalizasyonu yanı sıra kalsifikasyon ve nekrozun değerlendirilmesi amaçlanmaktadır (53)(54)(55)(56)(57)(58) .…”
Section: Peri̇feral Nöroblasti̇k Tümörlerunclassified